2023
DOI: 10.4081/aiua.2023.11238
|View full text |Cite
|
Sign up to set email alerts
|

Congenital penile curvature as a possible risk factor for the onset of Peyronie's disease, and psychological consequences of penile curvature

Abstract: Objective: To investigate a possible relationship between a history of congenital penile curvature (CPC) and Peyronie's disease (PD), and to characterize the psychological profile of patients suffering from PD, with or without concomitant CPC. Methods: We included 519 patients with Peyronie's disease (PD), of which 73 were found to have underlaying CPC. As a comparator population, we selected 2166 patients without PD, referring to our tertiary care clinic. In this population we detected 15 subjects with CPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Although no genome-wide association study (GWAS) studies to date have specifically examined genetic susceptibility to PD, other reported findings provide several possibly associated candidate genes. Other known intrinsic risk factors include aging and low testosterone level, while associations of the ABO blood group with congenital penile curvature (CPC) and PD have also been reported [ 177 , 184 ].…”
Section: Risk Factors For Pathogenesis Of Peyronie’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Although no genome-wide association study (GWAS) studies to date have specifically examined genetic susceptibility to PD, other reported findings provide several possibly associated candidate genes. Other known intrinsic risk factors include aging and low testosterone level, while associations of the ABO blood group with congenital penile curvature (CPC) and PD have also been reported [ 177 , 184 ].…”
Section: Risk Factors For Pathogenesis Of Peyronie’s Diseasementioning
confidence: 99%
“…Thus, CPC is considered to have a completely different pathology from PD, an acquired condition that causes obvious pathological changes in the TA. Recently, Paulis et al conducted a retrospective analysis of a clinical database from a single andrology clinic and found a history of CPC in 73 of 519 patients with PD (14.1%), whereas only 15 (0.7%) of 2166 in a comparator population without PD had such results [ 184 ]. These authors speculated that the presence of CPC is a risk factor for the subsequent development of PD, although the mechanisms underlying the association between the two diseases remain unclear.…”
Section: Risk Factors For Pathogenesis Of Peyronie’s Diseasementioning
confidence: 99%
“…Although there is no specific incidence of anxiety symptoms in PD in the literature, some studies report the presence of "emotional difficulties" and "distress" in about 80-81% of cases (34,35). In our recent study, we found that moderate-to-severe anxiety was present in 89.4% of PD patients (36).…”
Section: Psychological Consequences Of Pd and Cpmentioning
confidence: 57%
“…The scientific literature is rich in studies that have demonstrated the presence of numerous risk factors able to favor the onset of PD. These studies include the following risk factors: penile trauma, erectile dysfunction, congenital penile curvature, Dupuytren's disease, diabetes mellitus, dyslipidemia, obesity, hypertension, smoking, alcohol consumption, rheumatoid arthritis, psoriasis, and psoriatic arthritis (36,(53)(54)(55)(56)(57)(58). This is the first study that specifically investigates the association between PD and CP.…”
Section: Discussionmentioning
confidence: 99%